ONSET OF SUBDUCTION AS THE CAUSE OF RAPID PLIOCENE-QUATERNARY SUBSIDENCE IN THE SOUTH CASPIAN BASIN - Allen M.B.; Simmons M.; Anderson L.; Jones S.; Ismail-Zadeh A. (My University, 2002)
Backstripping a representative stratigraphic column from the northwest of the South Caspian basin shows that 2.4 km of tectonic subsidence has occurred since ca. 5.5 Ma, at 1.5–10 times the rate recorded in typical foreland basins. Roughly half the basin's sedimentary thickness of 20 km has accumulated in this time, while the upper part of the succession has begun to deform by buckle folding. The South Caspian basement appears to be either thick oceanic crust, or thinned, high-velocity continental crust. Seismicity and gravity data indicate that the basement is in the initial stages of subduction under the middle Caspian region to the north. We propose that basement subduction began ca. 5.5 Ma to create the major Pliocene-Quaternary subsidence. Subduction may have been triggered by a regional reorganization in the Arabia-Eurasia collision at that time, possibly following the construction of the Turkish-Iranian Plateau.
Keywords: Quaternary; Pliocene; Cenozoic::Quaternary; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная